1989
DOI: 10.2307/1130931
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Stressful Life Events and Adjustment in Elementary School Children: The Role of Social Support and Social Problem-Solving Skills

Abstract: This study investigated the relation between stressful life events and adjustment in elementary school children, with particular emphasis on the potential main and stress-buffering effects of social support and social problem-solving skills. Third through fifth graders (N = 361) completed social support and social problem-solving measures. Their parents provided ratings of stress in the child's environment and ratings of the child's behavioral adjustment. Teachers provided ratings of the children's behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
3
16

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(117 citation statements)
references
References 0 publications
2
95
3
16
Order By: Relevance
“…Although findings are sometimes inconsistent, studies have demonstrated the beneficial effects of social support on children and adolescents' achievement (Cauce, Hannan, & Sargeant, 1992;Dubow & Tisak, 1989;Dubow, Tisak, Causey, Hryshko, & Reid, 1991;Gutman & Midgley, 2000). Studies focusing on the achievement of poor and minority children, in particular, have emphasized the importance of having supportive relationships with teachers, peers, and other adults (e.g., Clark, 1983;Comer, 1980;Rutter, 1979).…”
Section: Social Support Factorsmentioning
confidence: 99%
“…Although findings are sometimes inconsistent, studies have demonstrated the beneficial effects of social support on children and adolescents' achievement (Cauce, Hannan, & Sargeant, 1992;Dubow & Tisak, 1989;Dubow, Tisak, Causey, Hryshko, & Reid, 1991;Gutman & Midgley, 2000). Studies focusing on the achievement of poor and minority children, in particular, have emphasized the importance of having supportive relationships with teachers, peers, and other adults (e.g., Clark, 1983;Comer, 1980;Rutter, 1979).…”
Section: Social Support Factorsmentioning
confidence: 99%
“…A number of studies have shown that social problem solving ability, either by itself, or together with social support, can reduce or minimize the impact of life stress on individuals (Dubow & Tisak, 1989;Dubow, Tisak, Causey, & Hryshko, 1991;D'Zurilla & Sheedy, 1991;Goodman, Gravitt, & Kaslow, 1995). Social problem solving abilities are found to moderate the relationship between negative life stress and measures of distress such as hopelessness (Bonner & Rich, 1988), anxiety (Nezu, 1986a), depressive symptoms (Nezu, 1986b), and behavioral and academic adjustment (Kang & Lee, 1992).…”
mentioning
confidence: 99%
“…Alternatif çözüm üretme ile özellikle çözüm için engel teşkil edebilecek durumlar tespit edilerek, 286 karşılaşılan problemin çözümüne bir adım daha yaklaşılmaktadır (D'Zurilla ve Nezu, 2010). Bununla birlikte farklı çözümler üretebilme becerisi, problemle karşılaşılan durumlarda stres ile başa çıkabilmeyi kolaylaştırmaktadır (Dubow ve Tisak, 1989;Özgülük ve Erdur Baker, 2010). Bu durumun daha sağlıklı çözümler üretebilmekte büyük bir önem taşıdığı düşünülmektedir.…”
Section: Duygusal Empati (De) Düzeylerine Ilişkin Bulgularunclassified